2013
DOI: 10.1517/14740338.2014.861816
|View full text |Cite
|
Sign up to set email alerts
|

Basiliximab: efficacy and safety evaluation in kidney transplantation

Abstract: There is a solid evidence that basiliximab can significantly decrease the risk of acute rejection in kidney transplant recipients without increasing adverse events. This can allow decreased dosage or avoidance of glucocorticoids and reduced dosage of calcineurin inhibitors. On the basis of efficacy, tolerability, ease of administration, and cost effectiveness, basiliximab may be considered the drug of choice for the prophylaxis of acute rejection in standard renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 71 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Novel therapies for AMR, possibly in addition to TPE and IVIG are now becoming available. These include newer medications such as anti‐CD20 for B cells (rituximab), proteasome inhibitors leading to plasma cell apoptosis (bortezomib), anti‐interleukin‐2 receptor antibodies (daclizumab, basiliximab), and anti‐CD52 (alemtuzumab). Anti‐complement therapy (eculizumab, recombinant human C1 esterase inhibitor) may also be possibilities in the future to interfere with the complement cascade initiated by antigen–antibody complexes, which has a potential to prevent complement‐mediated cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…Novel therapies for AMR, possibly in addition to TPE and IVIG are now becoming available. These include newer medications such as anti‐CD20 for B cells (rituximab), proteasome inhibitors leading to plasma cell apoptosis (bortezomib), anti‐interleukin‐2 receptor antibodies (daclizumab, basiliximab), and anti‐CD52 (alemtuzumab). Anti‐complement therapy (eculizumab, recombinant human C1 esterase inhibitor) may also be possibilities in the future to interfere with the complement cascade initiated by antigen–antibody complexes, which has a potential to prevent complement‐mediated cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, some evidence from registry data to suggest that the lower rejection rates might translate into better graft survival [121]. Pharmacoeconomic analysis has shown that these agents are cost effective in the early post-transplant period, and this is embodied in National Institute for Clinical Excellence (NICE) guidelines (https://www.nice.org.uk/guidance/ta85) [165]. …”
Section: Rationale For Clinical Practice Guidelines For Post-operativmentioning
confidence: 99%
“…1,2 The use of the non-T-cell depleting agents [IL-2 receptor antagonist (IL-2 RA) preparations] is still popular choices within kidney transplantation, but is generally recommended for use in lower immunologic risk patients. 68 …”
mentioning
confidence: 99%